Avoiding lodging in irrigated spring wheat. I. Stem and root structural requirements - Piñera-Chavez, F.J.; Berry, P.M.; Foulkes, M.J.; Jesson, M.A.; Reynolds, M.P. (Elsevier, 2016)
A model of the lodging process has been successfully adapted for use on spring wheat grown in North-West Mexico (NWM). The lodging model was used to estimate the lodging-associated traits required to enable spring wheat grown in NWM with a typical yield of 6 t ha−1 and plant height of 0.7 m to achieve a lodging return period of 25 years. Target traits included a root plate spread of 51 mm and stem strength of the bottom internode of 268 N mm. These target traits increased to 54.5 mm and 325 N mm, respectively, for a crop yielding 10 t ha−1. Analysis of multiple genotypes across three growing seasons enabled relationships between both stem strength and root plate spread with structural dry matter to be quantified. A NWM lodging resistant ideotype yielding 6 t ha−1 would require 3.93 t ha−1 of structural stem biomass and 1.10 t ha−1 of root biomass in the top 10 cm of soil, which would result in a harvest index (HI) of 0.46 after accounting for chaff and leaf biomass. A crop yielding 10 t ha−1 would achieve a HI of 0.54 for 0.7 m tall plants or 0.41 for more typical 1.0 m tall plants. This study indicates that for plant breeders to achieve both high yields and lodging-proofness they must either breed for greater total biomass or develop high yielding germplasm from shorter crops.